Effect of calcium chloride on sodium alginate on the restructuring of fish products - Nykyforov, Radion; Korenets, Yuriі; Frolova, Natalia; Kuzmin, Oleg (My University, 2019)
The purpose of this publication is to investigate the mechanism of the restructuring of fishery products using calcium chloride and sodium alginate.
Keywords: fish; carp; риба; короп; alginates; fillets; альгінати; філе; кафедра технології ресторанної і аюрведичної продукції